Economic Aspects of Italian Cactus Pear Production and Market - Basile, Filadelfio (Journal of the Professional Association for Cactus Development, 2001)
This study examines the main economic aspects of cactus pear production in Italy. In particular, following a brief introduction which places the work in the wider context of global trends for cactus pear production, the study presents a in depth analysis of demand trends and its determinants, supply and its utilisation, sales and marketing processes and price trends at the farm gate and wholesale levels. Overall, the recent expansion in production, in the face of a slight reduction in profitability, confirms the strength of this product in the market. This is despite the poor structure of marketing and trading institutions, and the lack of serious promotion efforts. In this context there appears to be a significant role for public intervention.